The Effect of Career Development and Organizational Culture on Employee Performance through Job Satisfaction at Bahasakuinggris in Pare, Kediri - Siti Durotul Khasanah; Arief Subyantoro; Yuni Siswanti (International Journal of Economics, Business and Innovation Research, 2025)
This study was conducted on employees of Bahasakuinggris in Pare, Kediri. The aim of this study is to examine the effect of career development and organizational culture on employee performance through job satisfaction. The population of this study consists of all 150 employees of Bahasakuinggris. The sample was taken using a census method. Data was collected by distributing a questionnaire via Google Forms, which was structured using a Likert scale, and analysed using Structural Equation Modelling (SEM) techniques on SmartPLS 3 software. The results of this study show that career development positively affects employee performance, organizational culture positively affects employee performance, and job satisfaction positively affects employee performance. Job satisfaction mediates the relationship between career development and employee performance, as well as the relationship between organizational culture and employee performance.